Potential Modulation of Vascular Function by Nitric Oxide and Reactive Oxygen Species Released From Erythrocytes - Rifkind, Joseph M.; Mohanty, Joy G.; Nagababu, Enika; Salgado, Maria T.; Cao, Zeling (Frontiers in Physiology, 2018)
The primary role for erythrocytes is oxygen transport that requires the reversible binding of oxygen to hemoglobin. There are, however, secondary reactions whereby the erythrocyte can generate reactive oxygen species (ROS) and nitric oxide (NO). ROS such as superoxide anion and hydrogen peroxide are generated by the autoxidation of hemoglobin. NO can be generated when nitrite reacts with hemoglobin forming an HbNO+ intermediate. Both of these reactions are dramatically enhanced under hypoxic conditions. Within the erythrocyte, interactions of NO with hemoglobin and enzymatic reactions that neutralize ROS are expected to prevent the release of any generated NO or ROS. We have, however, demonstrated that partially- oxygenated hemoglobin has a distinct conformation that enhances hemoglobin-membrane interactions involving Band 3 protein. Autoxidation of the membrane bound partially-oxygenated hemoglobin facilitates the release of ROS from the erythrocyte. NO release is made possible when HbNO+, the hemoglobin nitrite-reduced intermediate, which is not neutralized by hemoglobin, is bound to the membrane and releases NO. Some of the released ROS has been shown to be transferred to the vasculature suggesting that some of the released NO may also be transferred to the vasculature. NO is known to have a major effect on the vasculature regulating vascular dilatation. Erythrocyte generated NO may be important when NO production by the vasculature is impaired. Furthermore, the erythrocyte NO released, may play an important role in regulating vascular function under hypoxic conditions when endothelial eNOS is less active. ROS can react with NO and, can thereby modulate the vascular effects of NO. We have also demonstrated an inflammatory response due to erythrocyte ROS. This reflects the ability of ROS to react with various cellular components affecting cellular function.